PERANAN ULAMA DALAM PERKEMBANGAN ISLAM DI OGAN ILIR - Padila Padila (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2013)
Abstract: In  Ogan Ilir in South Sumatra about Century XIX and XX century there are many scholars who contributed to the spread of Islam. How to spread Islam is quite diverse, including through educational institutions, itinerant preaching, and the construction of a mosque, which served as the center of Islam. In the spread of Islam is not the least constraints faced by the propagator, in this case, mainly from the invaders, both from the colonial Dutch and Japanese. However, the efforts in spreading Islam and it still continues to concentrate more on education. Will be presented in this article what efforts have been made by scholars Ogan Ilir in the spread of Islam and its development, as well as whatever channel they use in preaching. Keywords:  Islamic defendant, Ogan Ilir Regional